1999
DOI: 10.1002/(sici)1097-4679(199909)55:9<1085::aid-jclp6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in schizophrenia on the WAIS-R NI sentence arrangement subtest

Abstract: Performance of participants diagnosed with schizophrenia on the Sentence Arrangement subtest of the WAIS-R NI and several tests sensitive to frontal lobe dysfunction was significantly poorer than that of manic depressive or control participants. Several measures of performance of patients diagnosed with schizophrenia on the WAIS-R NI Sentence Arrangement subtest appeared to support recent interpretations of the cognitive deficit seen in schizophrenia. These data represent the first demonstration of deficit per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Irrespective of illness phase and symptom severity, the speed of mental processing in BD patients seems to be slower [ 34 , 43 45 , 59 , 70 87 ]. Moreover, it has been reported that the speed of mental processing is less affected in comparison to schizophrenia [ 38 , 40 , 61 , 88 ], although there are some data suggesting the presence of a similar degree of impairment between patients with BD and patients with schizophrenia [ 89 ]. On the other hand, it has been suggested that there were no significant differences between depressed BD patients, euthymic BD patients and healthy controls in psychomotor speed [ 90 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of illness phase and symptom severity, the speed of mental processing in BD patients seems to be slower [ 34 , 43 45 , 59 , 70 87 ]. Moreover, it has been reported that the speed of mental processing is less affected in comparison to schizophrenia [ 38 , 40 , 61 , 88 ], although there are some data suggesting the presence of a similar degree of impairment between patients with BD and patients with schizophrenia [ 89 ]. On the other hand, it has been suggested that there were no significant differences between depressed BD patients, euthymic BD patients and healthy controls in psychomotor speed [ 90 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has been suggested a severe impairment in executive functions except reasoning during all phases of BD [ 34 , 36 , 43 45 , 48 , 70 , 72 , 73 , 75 77 , 86 , 87 , 90 , 94 , 101 103 , 108 , 109 , 111 , 120 122 , 129 , 143 , 146 , 149 , 190 , 195 , 197 209 ] and early during the course of BD [ 93 ], but the deficit is less pronounced in comparison to schizophrenia [ 38 , 40 , 61 , 89 , 116 , 122 , 210 ]. However, at least a subgroup of patients is as severely impaired as patients with schizophrenia [ 153 , 211 , 212 ].…”
Section: Reviewmentioning
confidence: 99%